1993
DOI: 10.1084/jem.177.3.751
|View full text |Cite
|
Sign up to set email alerts
|

HLA-A31- and HLA-Aw68-restricted cytotoxic T cell responses to a single hepatitis B virus nucleocapsid epitope during acute viral hepatitis.

Abstract: SummaryWe have recently developed the technology to identify and characterize the human histocompatibility leukocyte antigen (HLA) class I-restricted, CD8 + cytotoxic T lymphocyte (CTL) response to hepatitis B virus (HBV)-encoded antigens in patients with acute viral hepatitis. CTL are expanded in vitro by stimulation with HBV-derived synthetic peptides and selected by restimulation with a panel of HLA-matched stable transfectants that express the corresponding HBV protein. We have recently reported the existe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(119 citation statements)
references
References 37 publications
4
115
0
Order By: Relevance
“…The protection offered by immunity elicited by HBV vaccine, which is usually polyclonal in nature, may not be totally lost or severely affected in vivo by the substitution of only one amino acid. However, some individuals are known to have a more narrowly focused host immune response than others (Chisari & Ferrari, 1995 ;Missale et al, 1993 ;Penna et al, 1992). In these individuals, any loss of the limited responsive repertoire of the viral epitopes could accentuate the ability of the variant virus to evade the host immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The protection offered by immunity elicited by HBV vaccine, which is usually polyclonal in nature, may not be totally lost or severely affected in vivo by the substitution of only one amino acid. However, some individuals are known to have a more narrowly focused host immune response than others (Chisari & Ferrari, 1995 ;Missale et al, 1993 ;Penna et al, 1992). In these individuals, any loss of the limited responsive repertoire of the viral epitopes could accentuate the ability of the variant virus to evade the host immunity.…”
Section: Discussionmentioning
confidence: 99%
“…This type of CTL response is unusual, however, during HBV infection, when the CTL response is typically vigorous and multispecific during acute hepatitis and weak or undetectable during chronic hepatitis. 42,65,66,72 Accordingly, mutational inactivation of CTL epitopes is extremely uncommon during chronic HBV infection. 73 Nonetheless, strong, narrowly focused CTL responses do occur occasionally in these patients, 20 and in this setting viral escape mutations can occur.…”
Section: Mechanisms Of Hbv Persistencementioning
confidence: 99%
“…There is considerable evidence suggesting that HBV is not directly cytopathic (3), and that the hepatitis is caused by immune responses against virus-infected hepatocytes (4). In vitro studies have shown that hepatitis B surface antigen (HBsAg)-and hepatitis B core antigen (HBcAg)-expressing transfectants can serve as targets for MHC class I-restricted cytotoxic T lymphocytes (CTLs) that are generated from both acute and chronic hepatitis B patients (5)(6)(7)(8)(9)(10)(11)(12). In addition, expression of HBcAg in the cytoplasm and on the membrane of liver cells is positively correlated with the hepatitis activity (13,14).…”
Section: Introductionmentioning
confidence: 99%